The Changes in the Bishop Posts in the Czech Lands in the Period of the First World War - Smid, Marek (Historica Olomucensia, 2018)
The presented study The Changes in the Bishop Posts in the Czech Lands in the Period of the First World War deals with the assignment of bishop posts in Czech lands during the period of the First World War in the years 1914-1918. Vienna in war hardship and under the pressure from Berlin vigorously influenced ecclesial issues, which arrangement strengthen the centralistic and absolutistic character of the Habsburg estate. A visible proof of such influence were the interventions during the assignment of archbishops in the Czech lands in the middle of the war - L. Skrbensky was assigned in Olomouc, P. Huyn in Prague and N. Klein in Brno. The study deals with the given changes and its circumstances, while it analysis the causes and the consequences of the decisions, which by its decisive assertion of the Vienna candidates Lev Skrbensky from Hriste and Pavel Huyn distinctively infringed free election of ordinaries. The study proceeded from vast material in Historical archive of the State secretariat section for international relations in Vatican, Secret Vatican archive, Domestic, courtly and state archive in Vienna, State archive in Opava (Olomouc's branch), and National Archive in Prague and vast Czech, English, German and Italian literature.
Keywords: Holy See; Czech lands; bishops; World War I; 1914-1918